Highway bridge superstructure engineering LRFD approaches to design and analysis - Taly, Narendra (Taylor & Francis, Taylor & Francis Group, 2015)
Highway Bridge Superstructure Engineering: LRFD Approaches to Design and Analysis provides a detailed discussion of traditional structural design perspectives, and serves as a state-of-the-art resource on the latest design and analysis of highway bridge superstructures. This book is applicable to highway bridges of all construction and material types, and is based on the load and resistance factor design (LRFD) philosophy. It discusses the theory of probability (with an explanation leading to the calibration process and reliability), and includes fully solved design examples of steel, reinforced and prestressed concrete bridge superstructures. It also contains step-by-step calculations for determining the distribution factors for several different types of bridge superstructures (which form the basis of load and resistance design specifications) and can be found in the AASHTO LRFD Bridge Design Specifications.